The circular supply chains in smart cities: A catalyst for sustainable development - Fernando, Yudi; Sroufe, Robert; Tseng, Ming-Lang; Muhammad Shabir, Shaharudin; Wahyuni-TD, Ika Sari; Jawo, Muhammed (Taylor and Francis Ltd., 2025)
This study examines on how the circular supply chain (CSC) studies and its essential components enhance the sustainability of smart cities. It takes an interdisciplinary approach, blending the systematic review and social network analysis technique utilizing machine learning to identify the research paths. This study integrated the Biblioshiny application from the R package and conducted social network approach using factorial analysis based on machine learning techniques. The dataset from Scopus and Web of Science was used to develop beneficial relationships among circular economy practices, sustainability, and emerging smart city projects. The approach aids by principal component analysis to execute keyword parameters. The finding highlights the urban planners, technology developers, legislators considering implementing reverse logistics, remanufacturing and recycling to improve resource efficiency and reduce waste. The outcomes emphasize the future studies to broaden multidisciplinary analysis and practical applications, filling knowledge gaps and enhance the sustainable urban initiatives.